PENERAPAN SISTEM MANAJEMEN INFORMASI OBYEK PAJAK (SISMIOP) SEBAGAI SARANA PENINGKATAN PELAYANAN DAN PENERIMAAN PAJAK BUMI DAN BANGUNAN DI KABUPATEN BUOL - Kadadia, Ardiansyah M.; Sondakh, Jullie J.; Runtu, Treesje (Universitas Sam Ratulangi, 2016)
Tax property, urban and rural is a local tax was previously managed by the central government. In the year 2011 has been transferred to the regional governments together with SISMIOP. This is due lack of optimization PBB-P2 and SISMIOP as well as the central government gives full authority to local goverments so as to maximize the revenues from the tax. The purpose of this research is how the comparison application SISMIOP, is SISMIOP can improve service and reception as well as obstacless ancountered in the implementation of SISMIOP in Buol district. The method used for this research is the qualitative method that use observation, interviews with tax officials and documents processing. The results showed that application of SISMIOP in Buol district accordance with applicable rules and implementation SISMIOP can be more simple, fast and efficient. This is evidenced by the increasing aaceptance of the PBB-P2 once transferred to local government. Increased acceptance PBB-P2 can not be separated from continue doing the billing to the taxpayeer. Keyword: SISMIOP, Services, Income